Physiological changes in cycle rickshaw pullers after strenuous exercise - Debashis Manna; Sridhar Thakur; Chandan K Pradhan (International Journal of Occupational Safety and Health, 2012)
Background: Cycle Rickshaw is a human-powered transportation device. A large number of people remain engaged in the occupation of pulling cycle rickshaw.